Growth and Flowering Performance of Potted Gerbera, Gerbera Jamesonii L. Under Different Light Intensity - Uddin, AFM Jamal; Das, C; Shammy, F H; Foysal, M; Islam, M S (Journal of Bangladesh Academy of Sciences, 2012)
The influence of different light intensities (L0: full sunlight; L1: reduced sunlight; L2: 60% reduced sunlight) showed significant variations on growth and flower characteristics. Forty per cent reduced sunlight was more effective on growth and flower production than 60% reduced or in full sunlight. Tallest and thickest peduncles were produced (28.5 and 1.7 cm, respectively) with L1, similarly bigger flowers (6.0 cm diameter) were also found with L1 in comparison to L0 and L2. The maximum number of flowers per plant (15.6) was found from L1 and lowest (11.9) from L2. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12965 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 213-220, 2012